The Influence of Transfer to Local Government and Village Funds on Poverty and Village Development - Azizah, Siti Nur; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2026)
This study examines the impact of Regional Transfers (TKD) and Village Funds (DD) on poverty levels and village development in 29 districts in Central Java Province during the period 2019-2024. This study aims to evaluate the effectiveness of fiscal decentralization policies in supporting poverty alleviation and village empowerment efforts through an analysis of DAU, Physical and Non-Physical DAK, and DBH. Poverty levels are measured based on the number of poor people, while village development is measured using the Village Development Index. Quantitative methods were applied with panel data analysis through FEM regression and 2SLS simultaneous estimation to test the causal relationship between variables. The findings of this study reveal that DAU and DBH are effective in reducing poverty, while Non-Physical DAK and Village Funds contribute positively to village development. In addition, a significant reciprocal relationship between poverty and village development was revealed. The results of this study reinforce the theory of fiscal decentralization while providing recommendations for the formulation of more effective fiscal transfer policies in Indonesia.